Internalisasi Nilai-Nilai Keagamaan dalam Membentuk Komunikasi Keluarga Islami di Era Digital - Ditha Prasanti; Kismiyati El Karimah (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2018)
Family communication is a communication process experienced by every individual in the life of his family. Every good family will want to provide the best education and care for their children. It even manifests itself based on religious values in the family communication process. Religion is certainly the main foundation, not only in family communication, but in every aspect of human life. In this digital era, every family also has its own way in building religious values that are established through the process of family communication islamic. Therefore, the authors raised this research with the title "Internalization of Religious Values in Shaping Islamic Family Communications in the Digital Era". In this study, the authors use qualitative research method of case study. The data collection techniques used are participatory observation, in-depth interviews, and documentary tracking from various related sources. The result of the research shows that there is an effort to internalize religious values in shaping the Islamic family communication in this digital era which consists of: (1) The role of parent as communicator, very dominant in the pattern of family communication that is Islamic; (2) religious values embedded in Islamic families through the context of verbal and non verbal messages, ranging from education, health, association, and Islamic lifestyle; (3) The existence of social media use Whatsapp Group in spreading the message containing religious values to other family member